Economic analysis of oral cephalosporins in the Indian market - Karve, Ashwini V.; Paul, Kumardeep B. (International Journal of Research in Medical Sciences, 2016)
Background: Bacterial infections require appropriate and affordable treatment. A number of antimicrobial formulations are available in the Indian scenario. Affordable prescriptions improve compliance rate of the patients. This study was planned to evaluate & analyse the variation in the cost of oral cephalosporins (single and combination) in the Indian market. Methods: Cost per tablet or capsule of cephalosporins being manufactured by different companies, in the same strength and dosage forms was obtained from two drug compendia. The difference in the maximum and minimum price and percentage variation in price was calculated. Results: There are a number of companies manufacturing a particular drug, eg. Tab Cefixime (200 mg) - 127 companies, Tab Cefpodoxime (200 mg) - 106 companies, Cap Cefalexin (500 mg) - 38 companies and amongst the combinations; Tab Cefixime (200 mg) + Tab Clavulanate (125 mg) - 51 companies, Tab Cefpodoxime (200 mg) + Tab Clavulanate (125 mg) - 32 companies. A wide variation was found amongst the drugs ranging from 1746% for Tab Cefpodoxime (200 mg) to just 8.4% for Tab Cefdinir (100 mg). A similar variation existed for the combination drugs 9900% for Tab Cefixime (250 mg) + Tab Ornidazole (500 mg) and 42.1% for Tab Cefpodoxime (200 mg) + Tab Ofloxacin (200 mg). Conclusions: This study shows a wide price variation of the same drugs manufactured by different companies. The manufacturing companies must aim to reduce the price variation while maintaining the quality and therapeutic efficacy in order to benefit patients and practitioners.